METEOR OBSERVATIONAL DATA VISUALISATION IN THE EQUATORIAL COORDINATE SYSTEM USING INFORMATION TECHNOLOGY - Golovashchenko, V. A.; Kolomiyets, S. V. (Одеські астрономічні публікації, 2017)
As a result of dynamic evolution of IT industry and astronomical research in the XXI century, which have resulted in obtaining large and complex data sets known as Big Data (e.g. data from the European Space Agency missions, such as GAIA mission, etc.), as well as due to rapid development of computer technologies, astronomy and computer science have become closely linked to each other. In the XXI century, Information technology has become an essential part of understanding the world around. This paper presents a solution to the problem of meteor data representation in the second equatorial coordinate (RA-Dec) system using Information Technology. Such a visualisation solution is needed to analyse the results of experiments based on the radar observations conducted in 1972-1978 (stage 1 – the data obtained in 1972 comprise 10,247 meteor orbits), which have been accumulated and stored in the Meteor Database of the Kharkiv National University of Radio Electronics (KNURE). A sample set of data with their characteristicsand details about their delivery has been presented by (Kashcheyev & Tkachuk, 1980). An electronic calculator application was developed by employing the model of data visualisation in the form of celestial hemispheres using the object-oriented programming language C#.